2021
DOI: 10.1101/2021.05.13.443781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for template switching by a group II intron-encoded non-LTR-retroelement reverse transcriptase

Abstract: Reverse transcriptases (RTs) can template switch during cDNA synthesis, enabling them to join discontinuous nucleic acid sequences. Template switching plays crucial roles in retroviral replication and recombination, is used for adapter addition in RNA-seq, and may contribute to retroelement fitness by enabling continuous cDNA synthesis on damaged templates. Here, we determined an X-ray crystal structure of a template-switching complex of a group II intron RT bound simultaneously to an acceptor RNA and donor RN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 65 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Previous findings showed that this activity is dependent upon the RT0 loop, a distinctive conserved structural feature of non-LTR-retroelement RTs, with deletions in the RT0 loop inhibiting the templateswitching activity but not the primer extension activity of both GII and insect R2 element RTs (Jamburuthugoda and Eickbush, 2014; Stamos et al, 2017; Lentzsch et al, 2019). A recent X-ray crystal structure of a template-switching complex of GII RT revealed the structural basis for this activity by showing that the annealing of short base-pairing interactions between the donor and acceptor nucleic acids occurs in a binding pocket that is formed by the RT0 and fingertips loops and is absent in retroviral RTs (Lentzsch et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous findings showed that this activity is dependent upon the RT0 loop, a distinctive conserved structural feature of non-LTR-retroelement RTs, with deletions in the RT0 loop inhibiting the templateswitching activity but not the primer extension activity of both GII and insect R2 element RTs (Jamburuthugoda and Eickbush, 2014; Stamos et al, 2017; Lentzsch et al, 2019). A recent X-ray crystal structure of a template-switching complex of GII RT revealed the structural basis for this activity by showing that the annealing of short base-pairing interactions between the donor and acceptor nucleic acids occurs in a binding pocket that is formed by the RT0 and fingertips loops and is absent in retroviral RTs (Lentzsch et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, MMEJ and template switching are analogous in requiring the annealing of short microhomologies between two nucleic acid substrates and using the 3' end of one of the annealed strands as a primer for initiating DNA synthesis on the other. A difference, however, is that end-to-end template switching by group II intron RTs is optimal for annealing of a single base pair, while longer base-pairing interactions are inhibitory (Lentzsch et al, 2019), likely reflecting that the 3' ends of the donor and acceptor nucleic acid bind after RT core closure in a tightly constrained binding pocket formed by the RT0 loop and the fingertips loop (Lentzsch et al, 2021). By contrast, the annealing of longer microhomologies, such as those typically used for MMEJ, is more akin to the mechanism used for binding and annealing primers for primer extension, as evidenced by the findings that WT G2L4 and GII A/I RT with I at the active site favors the use of shorter primers and microhomologies, while GII and G2L4 I/A RTs with A at the active site enables more efficient use of longer primers or microhomologies (Figure 3A and C, Figure S10, and Figure S13B and C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations